Sustainability In Business Education Through Internationalisation: Challenges and the Roles - GHANI, NAZIFA ABD; TEO, POH-CHUIN; MAHADI, NOMAHAZA (The journal of contemporary issues in business and government, 2021)
The purpose of this paper aims to review the prior literature in examining the challenges and the roles that business education play in achieving sustainability. It also explains how internationalisation is applied to help business schools sustain in an ever-changing and global environment. Business education research shows that the extant of internationalisation has begun to expand since the mid-nineties. Broad differences of internationalisation approaches are taken in its internationalisation implementation among business education across the globe. Heading towards an emerging global knowledge economic world with an increasingly competitive global environment, changes is required in sustaining business education. This force business schools to revise the purpose of its establishment to integrate the international dimension to the development of students' skills. Through the current global situation, there has been a high pressure and challenges for business education. These involved touching all elements of valued-added networks in its internationalisation for developments of global business graduates with skills for sustainability in business education.